Effects of different proteins and maltodextrin combinations as wall material on the characteristics of Cornus officinalis flavonoids microcapsules - Zhao, Mengyue; Cao, Weiwei; Li, Linlin; Ren, Aiqing; Ang, Yuan; Chen, Junliang; Bhandari, Bhesh; Wang, Zhe; Ren, Xing; Ren, Guangyue; Duan, Xu (Frontiers in Nutrition, 2022)
Flavonoids from Cornus officinalis (CO) have antioxidant, anti-inflammatory and hypoglycemic activities. However, flavonoid instability limits its application in food and pharmaceutical industries. In this study, Cornus officinalis flavonoids (COF) microcapsules were prepared by using a combination of whey isolate protein (WPI), soy isolate protein (SPI), gelatin (GE) and maltodextrin (MD) as wall materials, respectively. Meanwhile, the encapsulation efficiency, moisture content, solubility, density, fluidity, color, particle size, thermal stability and microstructure as well as the antioxidant capacity of microcapsules were assessed. When the protein/MD ratio was 3:7, three kinds of combined wall materials realized high encapsulation efficiency (96.32%-98.24%). Among all the wall material formulations, microcapsules prepared with WPI-MD combination possessed best quality and thermal behavior. Compared with other wall material combinations, the microcapsules with WPI-MD wall ratio at 3:7 had lower particle size (7.17 μm), lower moisture content (6.13%), higher encapsulation efficiency (98.24%), better water solubility index (90.1%), higher thermal stability (86.00°C), and higher DPPH scavenging capacity (6.98 mg Vc/g), and better flowability. Results suggested that WPI and MD could be better wall materials applied in encapsulating COF.